Association of Serum Lipid Profile With Coronary Computed Tomographic Angiography–derived Morphologic and Functional Quantitative Plaque Markers. Issue 1 (January 2019) - Baumann, Stefan; Kryeziu, Philipp; Tesche, Christian; Shuler, Darby C.; Becher, Tobias; Rutsch, Marlon; Behnes, Michael; Stach, Ksenija; Jacobs, Brian E.; Renker, Matthias; Henzler, Thomas; Haubenreisser, Holger; et al.
Abstract : Purpose: Recent advances in image quality of coronary computed tomographic angiography (cCTA) have enabled improved characterization of coronary plaques. Thus, we investigated the association between quantitative morphological plaque markers obtained by cCTA and serum lipid levels in patients with suspected or known coronary artery disease. Materials and Methods: We retrospectively analyzed data of 119 statin-naive patients (55±14 y, 66% men) who underwent clinically indicated cCTA between January 2013 and February 2017. Patients were subdivided into a plaque and a no-plaque group. Quantitative and morphologic plaque markers, such as segment involvement score, segment stenosis score, remodeling index, napkin-ring sign, total plaque volume, calcified plaque volume, and noncalcified plaque volume (NCPV) and plaque composition, were analyzed using a semiautomated plaque software prototype. Total cholesterol, low-density lipoprotein (LDL), high-density lipoprotein, low-density lipoprotein/high-density lipoprotein ratio, and triglycerides were determine in both groups. Results: Higher age (61±11 y vs. 52±14 y, P <0.0001) and a higher likelihood of male gender (77% vs. 56%, P <0.0001) were observed in the plaque group. Differences in lipid levels were neither observed for differentiation between plaque presence or absence, nor after subcategorization for plaque composition. LDL serum levels >160 mg/dL correlated with higher NCPV compared with patients with LDL between 100 and 160 mg/dL (112 vs. 27 mm 3, P =0.037). Other markers were comparable between the different groups. Conclusion: Statin-naive patients with known or suspected coronary artery disease did not show differences in lipid levels related to plaque composition by cCTA. Patients with plaques tended to be men and were significantly older. High LDL levels correlated with high NCPV.